Simulation Data Acquisition and Control for LNG Custody Transfer Based on ISO 8943 - Muhammad Arman; Edi Wahyu Sri Mulyono; Muhamad Anda Falahuddin; Wirenda Sekar Ayu (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
Liquefied Natural Gas (LNG) is a complex mixture of low-molecular-weight hydrocarbons with nitrogen as a principal inert impurity. Nowadays, the instrumentation control tools are needed in LNG Commercialization to ensure the LNG is safely transported, while minimizing the energy losses across the network. This research was a preliminary design that used LNG custody transfer control tools referred the ISO 8943:2007 standard. The temperature was measured by thermocouple (Rosemount transmitter 3144 series), while the pressure was measured using pressure transmitter (Rosemount transmitter 3051 series). The simulated signal temperature was done by temperature control box, while the simulated pressure was represented by WIKA pressure calibrator. Data from transmitter was sent to the LabVolt 9063 series that has data acquisition for Software Development Kit (SDK) enabled. Previously, the LabVolt 9063 did not recognized the signal from the transmitter. The SDK software bridged the LabVolt hardware with the LabView software. In the simulated system, temperature alarm will be triggered when the temperature value exceeds 20oC. For simulated pressure, the alarm will respond if pressure value exceeds 30 psi. From the results of this research, the communication between hardware and software worked properly. The data acquisition system was stable during the data collection stage, processing and displaying. In addition, the alarm indicator for both temperature and pressure was met within the threshold value.